ANALISA KINERJA NATURAL DRAFT COOLING TOWER DI PPSDM MIGAS CEPU - Putirulan, Tesya; Waas, Kristofol; Loppies, Leslie S; Lopuhaa, Agustinus Oktovianus (Jurusan Teknik Mesin, 2024)
Human resource development center (PPSDM) a series of production processes such as boiler, power plants, coal testing sites, water treatment, fire and safety, pumps, welding workshops, distribution sites and refinery units, one of which is the cooling tower. The cooling tower is part of the power generation system that has a function as a heat exchanger between hot water coming out of the condenser and air so that the water has a lower temperature and can be reused in the condesation proses. The reseach on natural draf cooling tower in PPSDM migas aims to find parameters that affect the performance of natural draf cooling tower such as efficiency, make up water and also the heat transfer capacity of the cooling tower unit. In this writing, researchers use direct research methods in the field to find out the phenomena that occur in the colling Tower. While the performance of the natural draft cooling tower is calculated using the calculation method. The research results show an actual of 82,61 %, the recorded cooling capacity is 2417,941 kJ/s and the make up water value is 24.03 %Keywords: Cooling tower, Range, Approach, Effectiveness, Cooling Capacity, Make-Up Water.